State Judges As Guardians of Federalism: Resisting the Federal Arbitration Act's Encroachment on State Law - David S. Schwartz (Washington University Journal of Law & Policy, 2004)
Federalism is a battle often waged in the courts. State judges have a special role in this battle, because, unlike their federal counterparts, they are sworn to uphold not one, but two constitutional systems. In this Essay I argue that two principled tools of statutory interpretation designed to safeguard state autonomy in the name of federalism—the doctrine of constitutional avoidance and the presumption against preemption—have been ignored, and indeed violated, by the federal courts in Federal Arbitration Act (“FAA”) preemption cases. I argue further that it is incumbent on state court judges to use these tools pursuant to their dual constitutional duties, which authorize and require them (1) to interpret federal statutes independently in the absence of a controlling Supreme Court precedent; and (2) to give due regard to the interests of their states in the enforcement of state laws in the absence of a clear congressional mandate to preempt those laws. This requires state courts to construe both the FAA itself and the U.S. Supreme Court’s FAA preemption precedents as narrowly as good faith permits.
Keywords: Arbitration clauses (Contracts); Exclusive & concurrent legislative powers; Law -- Interpretation & construction